Antibacterial Activity of ZnO/Geopolymer Composite Granules and Their Potential Application in Water Treatment - Maulitia, Ziyan Tirta; Angelina, Putri Nur; Sari, Pipit Erlita; Sugiarti, Sri; Arief, Irma Isnafia; Abidin, Zaenal (Makara Journal of Science, 2025)
Water pollution has become a major global concern owing to its complexity and widespread impact. Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) are the most common bacterial contaminants in water sources, which pose significant threats to public health. To mitigate water contamination by these pathogenic microorganisms, developing and implementing effective water treatment technologies are essential. A promising approach involves using antibacterial water filtration systems. Herein, zinc oxide (ZnO) nanoparticles were synthesized via hydrothermal and precipitation methods as antibacterial agents for water treatment. These preparation methods required considerably low synthesis time. A capping agent was used to control nanoparticle growth and produce small nanoparticles. The synthesized ZnO nanoparticles were added in the surface of geopolymers to obtain ZnO/geopolymer composite granules, which improved their suitability for water filtration. The antibacterial activity of the ZnO nanoparticles and their composite granules was evaluated. Results indicated that synthetic ZnO exhibited superior antibacterial performance than commercial ZnO against S. aureus (gram-positive) and E. coli (gram-negative). Furthermore, incorporating either commercial or synthetic ZnO into the geopolymer matrix moderately enhanced the antibacterial activity of the resulting material. Notably, the addition of as low as 5 wt.% ZnO was sufficient to significantly improve the antibacterial efficacy of the composite. This finding highlights the potential of ZnO in water treatment applications.